"الإرهاب" الجهادي التكفيري في سورية - محفوض, زهير (Latakia University Journal - Economic and Legal Sciences Series, 2016)
في ظلّ ما تتعرّض له سورية من "إرهاب" على يد الجماعات الجهادية التكفيرية، وفي ظل الدعم غير المحدود لها من قبل الولايات المتحدة وتركيا والسعودية وغيرها، يأتي هذا البحث ليسلط الضوء على الخلفية العقائدية لـ"إرهاب" هذه الجماعات، وأهم العوامل التي أدت لانتشار فكرها عالميا وداخل سورية، وكيف لعبت ازدواجية المعايير في التعامل الدولي مع "الإرهاب" دورا في استمراره وزيادته. وتوصل البحث إلى أن الجماعات الجهادية التكفيرية تستند في منهجها إلى إرث "جماعة الإخوان المسلمين" والفكر الوهابي التكفيريَين، وتوصل أيضا إلى أن أهم عوامل انتشار الفكر التكفيري الجهل والبطالة والدعم السعودي والغربي المالي والإعلامي وغيرها، وأن الدول الداعمة لهذه الجماعات تستثمر نشاطها الإرهابي لتحقيق مصالحها أو للحفاظ عليها. In light of the expiatory jihadist groups’ terrorism against Syria and under the unlimited support from the United State, Turkey, Saudi Arabia and many other countries, this study tries to shed light on the ideological background of the terrorism of these groups and on the most important factors that led to the spread of their thoughts globally and within Syria. It also talks about how double standards has played a role in the international dealing with the terrorism in Syria and in its continuation and increasing. This research found that the jihadist groups depend – in their approach – on the legacy of “the Muslim Brotherhood" and on the Wahhabi expiatory thought. It also found that ignorance, unemployment, the media and the financial support from Saudi Arabia and from the West are the most important factors of the spread of expiatory thought. Besides, countries that support these groups invest their terrorist activity either to achieve their interests or to preserve them.